PERSPEKTIF GENDER SISWA SMK POKOK BAHASAN BARISAN DAN DERET - Solikhotur Rofiah (Universitas Asahan, 2020)
The purpose of this study is to describe the activities of students in solving mathematical problems in terms of gender. This research is in the form of a descriptive qualitative research. The instrument used in this study was a written test with a total of 6 questions adopted from the thesis. The subjects of this study were students of class XII Multimedia SMK Al-Ihsan Batujajar consisting of 2 male students and 2 female students. The results of this study indicate that the material sequence and series in understanding the concept of male students is higher than female students. But the level of development of the knowledge activities of male and female students is still at the same level.